2014
DOI: 10.1302/0301-620x.96b3.31421
|View full text |Cite
|
Sign up to set email alerts
|

The orthopaedic aspects of mycetoma

Abstract: This article presents an overview of mycetoma and offers guidelines for orthopaedic surgeons who may be involved in the care of patients with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 27 publications
6
52
0
Order By: Relevance
“…Some cases reported to have a bony involvement (15%), which complicates clinical management, leaving surgical amputation as the most likely treatment option. A similar finding was reported by Fahal, et al who found bone destruction in 794 cases (17%), but higher rate of bony involvement was reported in case report which was found in 5 patients out of 6 (Fahal et al 2014b). …”
Section: Discussionsupporting
confidence: 88%
“…Some cases reported to have a bony involvement (15%), which complicates clinical management, leaving surgical amputation as the most likely treatment option. A similar finding was reported by Fahal, et al who found bone destruction in 794 cases (17%), but higher rate of bony involvement was reported in case report which was found in 5 patients out of 6 (Fahal et al 2014b). …”
Section: Discussionsupporting
confidence: 88%
“…It is a chronic, specific, granulomatous, progressive subcutaneous inflammatory disease that spreads to involve the skin, deep structures and bones [4,5]. The disease is caused by true fungi or by certain bacteria and hence it is usually classified into eumycetoma and actinomycetoma, respectively [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The infection usually progresses slowly over many years and it is commonly painless and that may contribute to the late presentation of many patients [2,18]. The painless subcutaneous mass, multiple sinuses and discharge with grains is distinctive of this infection [1] Young adult males in the age range 20–40 years are more frequently affected [2,4]. Farmers, workers and students are affected most but no occupation is exempted [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…7 Management for maduramycosis entails extensive debridement of the infected tissue combined with prolonged antifungal therapy with ketoconazole (400-800 mg/day) or itraconazole (400 mg daily). [8][9][10] Long treatment periods, financial burden from the treatment complicated by drug resistance results in frequent failure of medical management and increases the probability of a surgical intervention such as amputation. The use of potent, extended-spectrum triazoles such as Posaconazole (800 mg/day) has produced high cure rates (80%) with remission up to 2 years after treatment.…”
Section: Discussionmentioning
confidence: 99%